Adhesive sheet

A pressure-sensitive adhesive sheet with a crosslinked structure formed by active energy ray irradiation addresses the challenge of high adhesion and heat resistance in semiconductor manufacturing, enabling easy peelability and heat resistance.

JP2025007428APending Publication Date: 2025-01-17TOAGOSEI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108813
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Adhesive tapes used in semiconductor manufacturing processes face challenges with high adhesion performance that makes peeling difficult, especially under high-temperature conditions, and require easy peelability upon irradiation with active energy rays for efficient semiconductor device manufacturing.

Method used

A pressure-sensitive adhesive sheet containing an acrylic adhesive polymer with specific functional groups and a hydrogen abstraction type photopolymerization initiator, forming a crosslinked structure upon irradiation to enhance peelability and heat resistance.

Benefits of technology

The adhesive sheet maintains high adhesion before irradiation and easy peelability after irradiation, ensuring effective peeling and heat resistance, suitable for semiconductor manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007428000002
    Figure 2025007428000002
  • Figure 2025007428000003
    Figure 2025007428000003
  • Figure 2025007428000001
    Figure 2025007428000001
Patent Text Reader

Abstract

To provide an adhesive sheet which exhibits easy peelability by irradiation with an active energy ray and has excellent heat resistance.SOLUTION: There is provided an adhesive sheet provided with an adhesive layer, wherein the adhesive layer is formed by an active energy ray curable adhesive composition which contains an acrylic adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator and contains no compound having two or more reactive unsaturated bonds in one molecule, the acrylic adhesive polymer (A) has at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon atom, a secondary amino group and a tertiary amino group in the side chain, the content of the hydrogen abstraction type photopolymerization initiator is 0.1 pts.mass or more and 50 pts.mass or less based on 100 pts.mass of the acrylic adhesive polymer (A) and the gel fraction based on the acrylic adhesive polymer (A) of the adhesive layer is 20% or more and 90% or less before lamination to an adherend.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]

[0002] Adhesives are processed into various forms such as tapes, labels, etc., and are used in a wide range of applications. In recent years, in response to advances in electronics technology, adhesive sheets have also been used in the manufacturing process of semiconductor devices for the purposes of improving the ease of handling during semiconductor manufacturing and further improving the performance of semiconductor elements (see, for example, Patent Document 1 and Patent Document 2).

[0003] Patent Document 1 discloses a heat-resistant temporary adhesive tape having an adhesive layer formed of an adhesive layer-forming material containing an acrylic polymer, an energy ray polymerizable oligomer, a polymerization initiator, and a crosslinking agent, the adhesive layer having a weight loss rate of the polymerization initiator measured by thermogravimetry of a predetermined value or less. Patent Document 2 discloses an adhesive tape having an adhesive layer containing a (meth)acrylic polymer and a photopolymerization initiator having a molar absorption coefficient of a predetermined value or more at a wavelength of 385 nm. These adhesive tapes are used for the purpose of temporary fixing or surface protection of electronic components, and when fixing of electronic components or surface protection is no longer required, the adhesive strength is weakened by irradiation with active energy rays, and the tape exhibits easy peelability.

[0004] In recent years, with the trend toward higher performance and thinner semiconductor devices, new semiconductor manufacturing technologies such as FOWLP (Fan Out Wafer Level Package) technology and three-dimensional integrated semiconductor (3D-IC) technology have been proposed. FOWLP is a technology that forms a redistribution layer on a semiconductor wafer and extends the terminals to the outside of the semiconductor chip, which is said to enable even higher performance and thinner semiconductor devices. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-31316 A [Patent Document 2] JP 2016-89045 A Summary of the Invention [Problem to be solved by the invention]

[0006] In the semiconductor manufacturing process by FOWLP, an adhesive tape is attached to a support substrate such as glass, a semiconductor chip is placed on the adhesive layer of the adhesive tape, and the semiconductor chip is temporarily fixed on the support substrate. Various lamination processes are then performed to form a laminate on the support substrate, and the laminate including the semiconductor chip is then peeled off from the support substrate. This method makes it possible to further reduce the thickness and improve the performance of semiconductor devices while improving the handleability during semiconductor manufacturing. In addition, a method of peeling off a laminate including a semiconductor chip from a support substrate by using active energy rays and weakening the adhesive strength of the adhesive layer by irradiation with active energy rays can simplify the peeling process and is also useful industrially.

[0007] The adhesive tape used in the above-mentioned semiconductor manufacturing process is required to exhibit high adhesive performance to the adherend when a laminate is formed on a support substrate, while being easily peelable from the support substrate when the laminate including the semiconductor chip is peeled off from the support substrate. In addition, the semiconductor manufacturing process may involve high-temperature heat treatment, for example, at 200°C or higher, and the adhesive tape used in the semiconductor manufacturing process is required to be resistant to lifting or foaming even when subjected to high-temperature heat treatment, and to have excellent heat resistance.

[0008] The present invention has been made in view of the above circumstances, and a main object of the present invention is to provide a pressure-sensitive adhesive sheet that exhibits easy peelability when irradiated with active energy rays and has excellent heat resistance. [Means for solving the problem]

[0009] The present inventors have conducted extensive research to solve the above problems, and have focused on the fact that irradiation with active energy rays promotes the formation of a crosslinked structure, thereby making the adhesive sheet easier to peel. Based on this focus, the inventors have found that the adhesive sheet can be improved in peelability while maintaining its heat resistance by introducing a specific structure into the polymer and using a specific additive, and have completed the present invention. Specifically, the present invention provides the following means.

[0010] [1] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer being formed from an active energy ray-curable pressure-sensitive adhesive composition containing an acrylic pressure-sensitive adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator, and not containing a compound having two or more reactive unsaturated bonds in one molecule, the acrylic pressure-sensitive adhesive polymer (A) having at least one group selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon, a secondary amino group, and a tertiary amino group in a side chain, the content of the hydrogen abstraction type photopolymerization initiator in the active energy ray-curable pressure-sensitive adhesive composition being 0.1 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the acrylic pressure-sensitive adhesive polymer (A), and the pressure-sensitive adhesive layer having a gel fraction based on the acrylic pressure-sensitive adhesive polymer (A) of 20% or more and 90% or less before being attached to an adherend. [2] The pressure-sensitive adhesive sheet according to [1], wherein the acrylic adhesive polymer (A) contains a structural unit (U) derived from a (meth)acrylic monomer having at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon (excluding the carbon atom constituting the carbon-carbon double bond in a methacryloyl group), a secondary amino group, and a tertiary amino group, and the content of the structural unit (U) in the acrylic adhesive polymer (A) is 10 mass % or more based on the total structural units of the acrylic adhesive polymer (A). [3] The pressure-sensitive adhesive sheet according to [1] or [2], wherein the acrylic pressure-sensitive adhesive polymer (A) contains a structural unit derived from a monomer represented by the following formula (1): CH2=CR 1 -C(=O)O-(R 2 O) n -R3 …(1) (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms; R 3 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms, and n represents an integer of 2 to 100. [4] The pressure-sensitive adhesive sheet according to any one of [1] to [3], wherein the glass transition temperature of the acrylic pressure-sensitive adhesive polymer (A) is −50° C. or higher and 0° C. or lower. [5] The pressure-sensitive adhesive sheet according to any one of [1] to [4], wherein the acrylic pressure-sensitive adhesive polymer (A) has a weight average molecular weight of 100,000 or more. [6] The pressure-sensitive adhesive sheet according to any one of [1] to [5], wherein the acrylic adhesive polymer (A) contains structural units derived from at least one selected from the group consisting of (meth)acrylic monomers having a boiling point of 100°C or less and (meth)acrylic monomers having a boiling point of 200°C or more, in an amount of 50 mass% or more relative to the total structural units of the acrylic adhesive polymer (A). [7] The pressure-sensitive adhesive sheet according to any one of [1] to [6], wherein the active energy ray-curable pressure-sensitive adhesive composition further contains a crosslinking agent. [7] The pressure-sensitive adhesive sheet according to any one of [1] to [7], wherein the pressure-sensitive adhesive layer has a weight loss rate of 5% by weight or less at 200°C, as measured by thermogravimetry under conditions of a heating rate of 20°C / min and a heating range of 25 to 350°C. [9] The pressure-sensitive adhesive sheet according to any one of [1] to [8], wherein the ratio (S2 / S1) of the peel strength (S1) before the pressure-sensitive adhesive sheet attached to an adherend is irradiated with active energy rays to the peel strength (S2) after the pressure-sensitive adhesive sheet attached to an adherend is irradiated with active energy rays to increase the gel fraction based on the acrylic adhesive polymer (A) of the pressure-sensitive adhesive layer to more than 90% is 0.7 or less.

[10] The pressure-sensitive adhesive sheet according to any one of [1] to [9], which is for use in a semiconductor manufacturing process. Effect of the Invention

[0011] According to the present invention, a pressure-sensitive adhesive sheet can be obtained which can be easily peeled off from an adherend by irradiation with active energy rays and which has excellent heat resistance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram showing an example of an adhesive sheet. [Diagram 2] 1A to 1C are diagrams showing an example of a method of using the adhesive sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. In this specification, "(meth)acrylic" means acrylic and / or methacrylic. "(meth)acrylate" means acrylate and / or methacrylate.

[0014] <Adhesive sheet> The pressure-sensitive adhesive sheet of the present invention (hereinafter also referred to as "the pressure-sensitive adhesive sheet") comprises a pressure-sensitive adhesive layer formed from an active energy ray-curable pressure-sensitive adhesive composition containing an acrylic pressure-sensitive adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator. The pressure-sensitive adhesive sheet has high adhesive strength when attached to an adherend, but the adhesive strength decreases when the pressure-sensitive adhesive layer is irradiated with active energy rays after the pressure-sensitive adhesive layer is attached to the adherend, and the sheet exhibits easy peelability.

[0015] <Gel fraction> Before being stuck to the adherend, the pressure-sensitive adhesive layer of this pressure-sensitive adhesive sheet has a gel fraction based on the acrylic adhesive polymer (A) in the range of 20% to 90%. If the gel fraction of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive sheet before being stuck to the adherend is less than 20%, the heat resistance of the pressure-sensitive adhesive layer cannot be ensured, and the pressure-sensitive adhesive layer is likely to flow due to thermal load. In addition, the adhesive strength of the pressure-sensitive adhesive layer may not be sufficiently ensured. On the other hand, if the gel fraction of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive sheet before being stuck to the adherend exceeds 90%, when the pressure-sensitive adhesive layer is irradiated with active energy rays after being stuck to the adherend, the difference in peel strength before and after irradiation with active energy rays cannot be sufficiently large, and the pressure-sensitive adhesive layer has insufficient easy peelability.

[0016] From the viewpoint of obtaining a pressure-sensitive adhesive sheet having excellent heat resistance while ensuring adhesion before irradiation with active energy rays and easy peelability after irradiation with active energy rays after lamination with an adherend, the gel fraction of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive sheet before lamination with an adherend is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. The upper limit of the gel fraction of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive sheet before lamination with an adherend is preferably 85% or less, more preferably 80% or less, and even more preferably 75% or less, from the viewpoint of ensuring easy peelability. The preferred range of the gel fraction of the pressure-sensitive adhesive layer in the pressure-sensitive adhesive sheet before lamination with an adherend can be determined by appropriately combining the above-mentioned upper limit and lower limit. Specifically, it is preferably 30 to 85%, more preferably 40 to 80%, and even more preferably 50 to 75%. Details of the measurement method follow the method described in the examples below.

[0017] <Active energy ray-curable pressure-sensitive adhesive composition> Next, the active energy ray curable adhesive composition (hereinafter also referred to as "the composition") constituting the adhesive layer of the adhesive sheet will be described. The composition is an adhesive composition that contains an acrylic adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator, and does not contain a compound having two or more reactive unsaturated bonds in one molecule (hereinafter also referred to as "reactive unsaturated compound").

[0018] (Acrylic adhesive polymer (A)) The acrylic adhesive polymer (A) is a polymer mainly composed of structural units derived from (meth)acrylic monomers, and has adhesive properties. In this specification, the acrylic adhesive polymer (A) being "mainly composed" of (meth)acrylic monomers means that the ratio of structural units derived from (meth)acrylic monomers to all structural units derived from monomers constituting the acrylic adhesive polymer (A) (hereinafter also referred to as "total structural units" or "total monomer units") is preferably 50% by mass or more. From the viewpoint of increasing the adhesive strength of the acrylic adhesive polymer (A), the ratio of structural units derived from (meth)acrylic monomers is more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0019] The acrylic adhesive polymer (A) has at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon, a secondary amino group, and a tertiary amino group in the side chain. It is considered that by forming an adhesive layer using such an acrylic adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator and irradiating the adhesive layer with active energy rays, hydrogen is abstracted from the side chain portion of the acrylic adhesive polymer (A) to form a crosslinked structure via the hydrogen abstraction portion.

[0020] More specifically, by irradiating the pressure-sensitive adhesive layer formed by the present composition with active energy rays, radicals are generated in the pressure-sensitive adhesive layer by the hydrogen abstraction type photopolymerization initiator. This radical abstracts hydrogen from the side chain portion of the acrylic adhesive polymer (A) (more specifically, the ether group in the side chain, the CH bond adjacent to the secondary amino group or the tertiary amino group, the hydroxyl group, and the aliphatic tertiary carbon), generating a carbon radical and / or an oxygen radical. It is considered that the radicals thus generated couple with each other, thereby forming a crosslinked structure. In addition, it is considered that the crosslinking between the side chains forms a dense crosslinked structure in the pressure-sensitive adhesive layer, which can reduce the adhesive strength of the pressure-sensitive adhesive sheet. That is, after being attached to an adherend, the pressure-sensitive adhesive sheet maintains a high adhesive strength before being irradiated with active energy rays, and then, by being irradiated with active energy rays, a crosslinked structure is formed between or within the molecules of the acrylic adhesive polymer (A), which is considered to develop easy peelability.

[0021] Specifically, the acrylic adhesive polymer (A) preferably contains a structural unit (hereinafter also referred to as "structural unit (U)") derived from a (meth)acrylic monomer having at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon (excluding the carbon atom constituting the carbon-carbon double bond in the methacryloyl group), a secondary amino group, and a tertiary amino group. By carrying out polymerization using such a monomer, at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon, a secondary amino group, and a tertiary amino group can be easily introduced into the side chain of the polymer. In this specification, the term "aliphatic tertiary carbon" refers to a carbon having one hydrogen atom and three carbon atoms bonded thereto, at least one of the three bonded carbon atoms constituting an aliphatic hydrocarbon group. The ether group refers to a group in which one or more hydrogen atoms are directly bonded to at least one of the two carbon atoms bonded to "-O-" in the "hydrocarbon group-O-hydrocarbon group".

[0022] Specific examples of monomers constituting the structural unit (U) include (meth)acrylic acid alkoxyalkyl esters, (meth)acrylic acid esters having an aliphatic tertiary carbon, (meth)acrylic acid hydroxyalkyl esters, polyalkylene glycol mono(meth)acrylates, and amino group-containing (meth)acrylic acid esters.

[0023] Specific examples of these include alkoxyalkyl (meth)acrylates, such as methoxymethyl (meth)acrylate, ethoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, n-propoxyethyl (meth)acrylate, n-butoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, ethoxypropyl (meth)acrylate, n-propoxypropyl (meth)acrylate, n-butoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxybutyl (meth)acrylate, n-propoxybutyl (meth)acrylate, and n-butoxybutyl (meth)acrylate.

[0024] Specific examples of (meth)acrylic acid esters having an aliphatic tertiary carbon include isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and EO-modified 2-ethylhexyl (meth)acrylate.

[0025] Specific examples of hydroxyalkyl (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0026] A specific example of the polyalkylene glycol mono(meth)acrylate is a monomer represented by the following formula (1). CH2=CR 1 -C(=O)O-(R 2 O) n -R 3 …(1) (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms; R 3 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms, and n represents an integer of 2 to 100.

[0027] R in the above formula (1) 3 From the viewpoint of easy availability of raw materials, n is preferably an alkyl group or an aryl group.

[0028] Further specific examples of polyalkylene glycol mono(meth)acrylates include polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol-polypropylene glycol mono(meth)acrylate, polyethylene glycol-polytetraethylene glycol mono(meth)acrylate, methoxypolyethylene glycol mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, stearoxypolyethylene glycol mono(meth)acrylate, octoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, phenoxypolyethylene glycol mono(meth)acrylate, phenoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate, nonylphenoxypolyethylene glycol mono(meth)acrylate, nonylphenoxypolypropylene glycol mono(meth)acrylate, and nonylphenoxypolyethylene glycol-polypropylene glycol mono(meth)acrylate. Commercially available polyalkylene glycol mono(meth)acrylate products include, by product name, Aronix M-101A, M-102, M-113, M-120, and M-140 (all manufactured by Toagosei Co., Ltd.); the Blenmar PP series, AP series, PME series, and AME series (all manufactured by NOF Corporation).

[0029] Examples of amino group-containing (meth)acrylic acid esters include dimethylaminomethyl (meth)acrylate, diethylaminomethyl (meth)acrylate, 2-dimethylaminoethyl (meth)acrylate, 2-diethylaminoethyl (meth)acrylate, 2-(di-n-propylamino)ethyl (meth)acrylate, 2-dimethylaminopropyl (meth)acrylate, 2-diethylaminopropyl (meth)acrylate, 2-(di-n-propylamino)propyl (meth)acrylate, 3-dimethylaminopropyl (meth)acrylate, 3-diethylaminopropyl (meth)acrylate and 3-(di-n-propylamino)propyl (meth)acrylate.

[0030] In terms of having a large number of hydrogen abstraction sites and being easily crosslinked by irradiation with active energy rays, the (meth)acrylic adhesive polymer (A) preferably contains a structural unit derived from at least one selected from the group consisting of (meth)acrylic alkoxyalkyl esters, (meth)acrylic hydroxyalkyl esters, and monomers represented by the above formula (1), and more preferably contains at least a structural unit derived from a monomer represented by the above formula (1).

[0031] In the acrylic adhesive polymer (A), the content of the structural unit (U) is preferably 10% by mass or more based on the total structural units of the acrylic adhesive polymer (A) from the viewpoint of facilitating the formation of a crosslinked structure by irradiation with active energy rays. The content of the structural unit (U) is more preferably 15% by mass or more based on the total structural units of the acrylic adhesive polymer (A), more preferably 20% by mass or more, and even more preferably 25% by mass or more. There is no particular upper limit to the content of the structural unit (U), but from the viewpoint of improving adhesive performance, it is preferably 90% by mass or less based on the total structural units of the acrylic adhesive polymer (A), more preferably 85% by mass or less, even more preferably 80% by mass or less, even more preferably 75% by mass or less, and even more preferably 70% by mass or less.

[0032] The acrylic adhesive polymer (A) may further contain a structural unit (hereinafter also referred to as "other structural unit") different from the structural unit (U). Examples of monomers constituting the other structural units include (meth)acrylic acid alkyl esters, aliphatic cyclic esters of (meth)acrylic acid, aromatic esters of (meth)acrylic acid, epoxy group-containing (meth)acrylic acid esters, silyl group-containing (meth)acrylic acid esters, unsaturated acid anhydrides, (meth)acrylamide or derivatives thereof, nitrile group-containing (meth)acrylic acid esters, aromatic vinyl compounds and imide group-containing vinyl compounds, unsaturated carboxylic acids, etc.

[0033] Specific examples of these include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, and lauryl (meth)acrylate.

[0034] Specific examples of the aliphatic cyclic esters of (meth)acrylic acid include cyclohexyl (meth)acrylate, cyclododecyl (meth)acrylate, etc. Specific examples of the aromatic esters of (meth)acrylic acid include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxymethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, and 3-phenoxypropyl (meth)acrylate, etc.

[0035] Specific examples of epoxy group-containing (meth)acrylic acid esters include glycidyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate. Specific examples of silyl group-containing (meth)acrylic acid esters include trimethoxysilylpropyl (meth)acrylate, triethoxysilylpropyl (meth)acrylate, methyldimethoxysilylpropyl (meth)acrylate, and dimethylmethoxysilylpropyl (meth)acrylate. Specific examples of unsaturated acid anhydrides include maleic anhydride, itaconic anhydride, and citraconic anhydride.

[0036] Specific examples of (meth)acrylamide or a derivative thereof include (meth)acrylamide, tert-butyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, and (meth)acryloylmorpholine.

[0037] Specific examples of the nitrile group-containing (meth)acrylic acid ester include cyanomethyl (meth)acrylate, 1-cyanoethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-cyanopropyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, 4-cyanobutyl (meth)acrylate, 6-cyanohexyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, and 8-cyanooctyl (meth)acrylate.

[0038] Specific examples of aromatic vinyl compounds include styrene-based compounds such as styrene, α-methylstyrene, β-methylstyrene, vinylxylene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, pn-butylstyrene, p-isobutylstyrene, pt-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, p-hydroxystyrene, m-hydroxystyrene, o-hydroxystyrene, p-isopropenylphenol, m-isopropenylphenol, o-isopropenylphenol, o-vinylbenzoic acid, m-vinylbenzoic acid, p-vinylbenzoic acid, and divinylbenzene, as well as vinylnaphthalene.

[0039] Specific examples of the imide group-containing vinyl compound include maleimide compounds such as maleimide and N-substituted maleimide compounds; itaconimide compounds such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; N-methylcitraconimide, N-ethylcitraconimide, N-butylcitraconimide, N-octylcitraconimide, N-2-ethylhexylcitraconimide, and N -Cyclohexylcitraconimide, N-laurylcitraconimide, and other citraconimide compounds; N-(2-(meth)acryloyloxyethyl)succinimide, N-(2-(meth)acryloyloxyethyl)maleimide, N-(2-(meth)acryloyloxyethyl)phthalimide, N-(4-(meth)acryloyloxybutyl)succinimide, N-(4-(meth)acryloyloxybutyl)maleimide, N-(4-(meth)acryloyloxybutyl)phthalimide, and other (meth)acrylimide compounds. The acrylic adhesive polymer (A) may contain only one type of other structural unit, or two or more types.

[0040] Specific examples of unsaturated carboxylic acids include (meth)acrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, citraconic acid, cinnamic acid, and monoalkyl esters of unsaturated dicarboxylic acids (monoalkyl esters of maleic acid, fumaric acid, itaconic acid, citraconic acid, etc.).

[0041] From the viewpoint of improving adhesive performance, the acrylic adhesive polymer (A) preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester. Also, from the viewpoint of increasing the elastic modulus of the acrylic adhesive polymer (A) and improving heat resistance, the monomer constituting the structural unit derived from a (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl moiety with 1 to 8 carbon atoms, more preferably a (meth)acrylic acid alkyl ester having an alkyl moiety with 1 to 4 carbon atoms.

[0042] In the acrylic adhesive polymer (A), the ratio of the structural unit derived from (meth)acrylic acid alkyl ester is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, based on the total structural units of the acrylic adhesive polymer (A), from the viewpoint of improving adhesive performance. In the acrylic adhesive polymer (A), the upper limit of the ratio of the structural unit derived from (meth)acrylic acid alkyl ester is not particularly limited, but from the viewpoint of sufficiently performing crosslinking formation by irradiation with active energy rays, it is preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less, based on the total structural units of the acrylic adhesive polymer (A).

[0043] Regarding the monomer constituting the acrylic adhesive polymer (A), from the viewpoint of suppressing foaming or peeling from the adhesive layer when the adhesive sheet is subjected to a thermal load, the acrylic adhesive polymer (A) preferably contains a structural unit (hereinafter also referred to as "structural unit (W)") derived from at least one monomer selected from the group consisting of (meth)acrylic monomers having a boiling point of 100°C or less and (meth)acrylic monomers having a boiling point of 200°C or more. Specifically, the proportion of the structural unit (W) is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the total structural units of the acrylic adhesive polymer (A). In this specification, the boiling point of the monomer is a predicted value calculated by Fujitsu Limited's scientific research information management solution (ACD / Labs). In this specification, the boiling point is a value under atmospheric pressure.

[0044] In terms of increasing the elastic modulus of the acrylic adhesive polymer (A) and improving heat resistance, and in terms of being easily volatilized during the production process of the adhesive sheet and thus suppressing foaming from the adhesive sheet, the acrylic adhesive polymer (A) preferably contains a structural unit derived from a (meth)acrylic monomer having a boiling point of 100° C. or less (hereinafter also referred to as "structural unit (W1)"). Specifically, the proportion of the structural unit (W1) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the total structural units of the acrylic adhesive polymer (A). On the other hand, from the viewpoint of exhibiting excellent peelability by irradiation with active energy rays, the proportion of the structural unit (W1) is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less, based on the total structural units of the acrylic adhesive polymer (A).

[0045] In addition, from the viewpoint of exhibiting excellent peelability by irradiation with active energy rays and suppressing volatilization of monomers when thermal load is applied, the acrylic adhesive polymer (A) preferably contains a structural unit derived from a (meth)acrylic monomer having a boiling point of 200° C. or more (hereinafter also referred to as "structural unit (W2)"). Specifically, the proportion of the structural unit (W2) is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the total structural units of the acrylic adhesive polymer (A). In addition, from the viewpoint of improving adhesive performance, the proportion of the structural unit (W2) is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 65% ​​by mass or less, based on the total structural units of the acrylic adhesive polymer (A).

[0046] -Manufacture of acrylic adhesive polymer (A) The acrylic adhesive polymer (A) is not particularly limited in the manufacturing method, and can be obtained by a known manufacturing method. For example, the acrylic adhesive polymer (A) can be obtained by polymerizing the above-mentioned monomers by adopting a known radical polymerization method such as solution polymerization, suspension polymerization, emulsion polymerization, or bulk polymerization.

[0047] In the case of the solution polymerization method, the production method may be such that an organic solvent and monomers are charged into a reactor, a polymerization initiator is added, and the mixture is heated to 50 to 300° C. to polymerize.

[0048] The method of feeding each raw material including the monomer may be a batch-type initial lump-sum feeding in which all raw materials are fed at once, a semi-continuous feeding in which at least a portion of the raw materials are continuously fed into the reactor, or a continuous polymerization method in which all raw materials are continuously fed and at the same time the produced resin is continuously withdrawn from the reactor.

[0049] Examples of organic solvents used in the solution polymerization method include cyclic ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbon compounds such as benzene, toluene and xylene, esters such as ethyl acetate and butyl acetate, ketones such as acetone, methyl ethyl ketone and cyclohexanone, and alcohols such as methyl orthoformate, methyl orthoacetate, methanol, ethanol and isopropanol. As the organic solvent, one or more of these can be used. The amount of the organic solvent used is, for example, 1 to 50 mass% of the total amount of the monomers used in the polymerization relative to the total amount of the organic solvent and the monomers.

[0050] The polymerization initiator may be a known radical polymerization initiator such as an azo compound, an organic peroxide, or an inorganic peroxide, and is not particularly limited. Among these, an azo compound is preferred because it is easy to handle and does not easily cause side reactions during radical polymerization. An azo compound is preferred. In addition, a redox type polymerization initiator consisting of a known oxidizing agent and a known reducing agent may be used as the polymerization initiator. Furthermore, a known chain transfer agent may be used in combination with the polymerization initiator.

[0051] Specific examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane), and dimethyl 2,2'-azobis(2-methylpropionate).

[0052] Examples of organic peroxides include cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane.

[0053] Examples of inorganic peroxides include potassium persulfate and sodium persulfate. Examples of redox type polymerization initiators include those using sodium sulfite, sodium thiosulfate, sodium formaldehyde sulfoxylate, ascorbic acid, ferrous sulfate, etc. as a reducing agent and potassium peroxodisulfate, hydrogen peroxide, tert-butyl hydroperoxide, etc. as an oxidizing agent. In producing the acrylic adhesive polymer (A), the amount of the polymerization initiator used is, for example, 0.01 to 20 parts by mass relative to 100 parts by mass of the total monomers used in the polymerization.

[0054] Glass transition temperature The glass transition temperature (Tg) of the acrylic adhesive polymer (A) is preferably within the range of -80°C or more and 10°C or less. If the Tg of the acrylic adhesive polymer (A) is -80°C or more, it is preferable in that the cohesive force of the adhesive layer can be sufficiently increased and sufficient adhesiveness can be ensured. From the viewpoint of increasing the adhesiveness of the adhesive layer, the Tg of the acrylic adhesive polymer (A) is more preferably -60°C or more, even more preferably -50°C or more, and even more preferably -45°C or more.

[0055] On the other hand, if the Tg of the acrylic adhesive polymer (A) is 10° C. or less, it is preferable because a pressure-sensitive adhesive sheet with good conformability to the adherend can be obtained. The upper limit of the Tg of the acrylic adhesive polymer (A) is more preferably 5° C. or less, even more preferably 0° C. or less, even more preferably −5° C. or less, and particularly preferably −10° C. or less. The preferred range of the Tg of the acrylic adhesive polymer (A) is more preferably −60° C. or more and 5° C. or less, even more preferably −50° C. or more and 0° C. or less.

[0056] In this specification, the Tg of a polymer is a value determined from the intersection point between the baseline of a heat flux curve obtained using a differential scanning calorimeter (DSC) and the tangent point at the inflection point. Details of the measurement conditions are as described in the examples below. The Tg of a polymer can be arbitrarily selected by changing the type and composition of the constituent monomers.

[0057] ·Molecular weight characteristics The weight average molecular weight (Mw) of the acrylic adhesive polymer (A) is preferably 100,000 or more from the viewpoint of exerting sufficient cohesive force and good adhesiveness. When the Mw of the acrylic adhesive polymer (A) is 100,000 or more, sufficient adhesiveness and solvent resistance can be ensured. The Mw of the acrylic adhesive polymer (A) is more preferably 120,000 or more, even more preferably 150,000 or more, and even more preferably 200,000 or more.

[0058] The upper limit of Mw of the acrylic adhesive polymer (A) is not particularly limited, but from the viewpoint of ensuring good coating and handling properties when forming an adhesive sheet and further ensuring ease of production, it is preferably 3,000,000 or less, more preferably 2,000,000 or less, and even more preferably 1,500,000 or less. The range of Mw of the acrylic adhesive polymer (A) is preferably 100,000 or more and 3,000,000 or less, more preferably 150,000 or more and 2,000,000 or less, and even more preferably 200,000 or more and 1,500,000 or less. In this specification, the molecular weight of the polymer is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0059] The molecular weight distribution (Mw / Mn) of the acrylic adhesive polymer (A), which is expressed as the ratio of Mw to the number average molecular weight (Mn), is preferably 10.0 or less, more preferably 9.0 or less, from the viewpoint of easily obtaining good adhesion and suppressing the increase in viscosity of the adhesive composition. The lower limit of Mw / Mn of the acrylic adhesive polymer (A) is not particularly limited, and can be 1.0 or more. In this specification, Mw and Mn of the polymer are standard polystyrene equivalent values ​​obtained using gel permeation chromatography (GPC).

[0060] (Hydrogen abstraction type photopolymerization initiator) The hydrogen abstraction type photopolymerization initiator is a compound that generates radicals by abstracting hydrogen from other molecules when irradiated with active energy rays. Examples of the active energy rays include ultraviolet rays, visible light rays, and electron beams, and preferably ultraviolet rays or electron beams.

[0061] As the hydrogen abstraction type photopolymerization initiator, a known hydrogen abstraction type radical polymerization initiator can be used. Specific examples of the hydrogen abstraction type photopolymerization initiator include benzophenone, 2-methylbenzophenone, 3-methylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, 4-phenylbenzophenone, 4-(methylphenylthio)phenylphenylmethane, methyl-2-benzophenone, 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylphenylsulfonyl)propan-1-one, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, and 4-methoxy-4' -Dimethylaminobenzophenone and the like benzophenones; thioxanthones such as thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 1-chloro-4-propylthioxanthone, 3-[3,4-dimethyl-9-oxo-9H-thioxanthone-2-yl-oxy]-2-hydroxypropyl-N,N,N-trimethylammonium chloride, and fluorothioxanthone; as well as benzyl ketals, anthraquinone, ethyl anthraquinone, phenanthrenequinone, xanthone, and hydroxyacetophenone.

[0062] In addition, commercially available products can be used as the hydrogen abstraction type photopolymerization initiator. Specific examples thereof include OMNIPOL BP, OMNIPOL TX, OMNIRAD ASA, OMNIRAD 4PBZ, OMNIRAD 2702, OMNBB, OMNIRAD BMS, OMNIRAD EMK, OMNIRAD DETX, OMNIRAD ITX, OMNIRAD EDB, OMNIRAD EHA, OMNIRAD BP Flasks, OMNIRAD 4MBZ Flasks, and ESACURE 3644 (all manufactured by IGM RESINS).

[0063] In order to improve the sensitivity of the pressure-sensitive adhesive sheet to the active energy rays irradiated thereto, a benzoic acid-based or amine-based photosensitizer may be used in combination as necessary. As the hydrogen abstraction type photopolymerization initiator, one type may be used alone, or two or more types may be used in combination.

[0064] As the hydrogen abstraction type photopolymerization initiator, benzophenones can be preferably used among the above because of their high heat resistance.

[0065] In the present composition, the content of the hydrogen abstraction type photopolymerization initiator is 0.1 parts by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the acrylic adhesive polymer (A). If the content of the photopolymerization initiator is 0.1 parts by mass or more, it is preferable that a crosslinked structure can be formed using the acrylic adhesive polymer (A) by the radicals generated in the adhesive layer by irradiating the adhesive layer with active energy rays. From this viewpoint, the amount of the hydrogen abstraction type photopolymerization initiator in the present composition is more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more with respect to 100 parts by mass of the acrylic adhesive polymer (A).

[0066] In order to prevent the pressure-sensitive adhesive layer from becoming brittle due to excessive formation of a crosslinked structure by irradiation with active energy rays, the amount of the hydrogen abstraction type photopolymerization initiator contained in the composition is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the acrylic pressure-sensitive adhesive polymer (A). As the hydrogen abstraction type photopolymerization initiator, one type may be used alone, or two or more types may be used in combination.

[0067] (Reactive unsaturated compounds) This composition does not substantially contain a compound having two or more reactive unsaturated bonds in one molecule (reactive unsaturated compound). Specific examples of reactive unsaturated compounds include polyfunctional (meth)acrylic compounds. When an active energy ray curable adhesive composition containing a reactive unsaturated compound is used, in an adhesive sheet having an adhesive layer formed from the adhesive composition, when a heat load (for example, about 200°C) is applied, a reaction (crosslinking reaction) between the reactive unsaturated compounds in the adhesive layer progresses, which leads to an unintended decrease in strength of the adhesive layer, or the reactive unsaturated compound itself volatilizes, resulting in a decrease in heat resistance. However, in this specification, "free of reactive unsaturated compounds" does not exclude the reactive unsaturated compound being contained in a trace amount in this composition to the extent that it does not impair the effects of the present invention. Specifically, the content of the reactive unsaturated compound in this composition is 0.5% by mass or less, preferably 0.2% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.05% by mass or less, based on the total amount of the composition.

[0068] The present composition is different from the so-called syrup-type active energy ray curable adhesive composition in that it does not contain a reactive unsaturated compound. Here, the syrup-type active energy ray curable adhesive composition contains a polymer component that constitutes a part of the acrylic adhesive polymer in the adhesive layer and a monomer component that constitutes the remainder, and the active energy ray curable adhesive composition is irradiated with active energy rays to generate the acrylic adhesive polymer that is the main component of the adhesive layer. At least one of the monomer components contained in such a syrup-type active energy ray curable adhesive composition corresponds to the "reactive unsaturated compound" in the present invention.

[0069] (Other Ingredients) The composition may further contain components other than the acrylic adhesive polymer (A) and the hydrogen abstraction type photopolymerization initiator (hereinafter also referred to as "other components") within the range not impairing the effects of the present invention. Examples of the other components include a solvent, a crosslinking agent, a tackifier, a plasticizer, etc.

[0070] ·solvent The present composition is preferably a solvent-based adhesive composition further containing a solvent. The solvent contained in the present composition is preferably an organic solvent capable of dissolving the acrylic adhesive polymer (A). Specific examples of the organic solvent include aprotic polar solvents, phenolic solvents, alcoholic solvents, ester solvents, ketone solvents, ether solvents, and hydrocarbon solvents. The organic solvent may be one of these, or a mixed solvent of two or more of them. The solvent contained in the present composition is preferably at least one selected from the group consisting of ethyl acetate, butyl acetate, ethyl methyl ketone, and toluene.

[0071] Crosslinking agent When the acrylic adhesive polymer (A) has a crosslinkable functional group, a crosslinking agent (curing agent) capable of reacting with the crosslinkable functional group may be blended into the composition to adjust the gel fraction of the adhesive layer of the adhesive sheet. Examples of crosslinking agents include glycidyl-based compounds having two or more glycidyl groups, isocyanate-based compounds having two or more isocyanate groups, aziridine-based compounds having two or more aziridinyl groups, oxazoline-based compounds having oxazoline groups, metal chelate compounds, butylated melamine compounds, and the like. Among these, isocyanate-based compounds are preferred because they can form an adhesive layer with higher cohesive strength.

[0072] Specific examples of the crosslinking agent include glycidyl compounds such as polyfunctional glycidyl compounds, such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, tetraglycidylxylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and trimethylolpropane polyglycidyl ether.

[0073] Examples of isocyanate compounds include aromatic isocyanate compounds such as diphenylmethane diisocyanate (MDI), tolylene diisocyanate (TDI), naphthalene diisocyanate (NDI), p-phenylene diisocyanate (PPDI), xylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), and tolidine diisocyanate (TODI); hexamethylene diisocyanate (HDI), and lysine diisocyanate (LYS). aliphatic isocyanate compounds such as isophorone diisocyanate (IPDI), cyclohexyl diisocyanate (CHDI), hydrogenated XDI (H6XDI), and hydrogenated MDI (H12MDI); and modified isocyanate compounds such as urethane modified products, dimers, trimers, carbodiimide modified products, urea modified products, isocyanurate modified products, oxazolidone modified products, and isocyanate group-terminated prepolymers.

[0074] Examples of the aziridine compounds include 1,6-bis(1-aziridinylcarbonylamino)hexane, 1,1'-(methylene-di-p-phenylene)bis-3,3-aziridyl urea, ethylene bis-(2-aziridinyl propionate), 2,4,6-triaziridinyl-1,3,5-triazine, and trimethylolpropane-tris(2-aziridinyl propionate).

[0075] From the viewpoint of achieving a well-balanced improvement in the adhesive performance and tracking ability of the adhesive sheet, the content of the crosslinking agent in the composition is preferably 0 to 5 parts by mass, and more preferably 0 to 2 parts by mass, per 100 parts by mass of the acrylic adhesive polymer (A).

[0076] Tackifier The composition may further contain a tackifier. Examples of the tackifier include rosin derivatives such as rosin ester, gum rosin, tall oil rosin, hydrogenated rosin ester, maleic rosin, and disproportionated rosin ester; terpene-based resins mainly composed of terpene phenol resins, α-pinene, β-pinene, or limonene; coumarone-indene resins, hydrogenated aromatic copolymers, and phenolic resins. The tackifier may be used alone or in combination of two or more. The content of the tackifier is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and even more preferably 0 to 5 parts by mass, based on 100 parts by mass of the acrylic adhesive polymer (A).

[0077] Plasticizers The composition may contain a plasticizer. Examples of the plasticizer include phthalates such as di-n-butyl phthalate, di-n-octyl phthalate, bis(2-ethylhexyl) phthalate, and di-n-decyl phthalate; adipates such as bis(2-ethylhexyl) adipate and di-n-octyl adipate; sebacic acid esters; azelaic acid esters; paraffins such as chlorinated paraffin; glycols such as polypropylene glycol; epoxy-modified vegetable oils such as epoxidized soybean oil and epoxidized linseed oil; phosphates such as trioctyl phosphate and triphenyl phosphate; phosphites such as triphenyl phosphite; ester oligomers such as esters of adipic acid and 1,3-butylene glycol; low molecular weight polymers such as low molecular weight polybutene, low molecular weight polyisobutylene, and low molecular weight polyisoprene; and oils such as process oil and naphthenic oil.

[0078] The content of the plasticizer is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and further preferably 0 to 5 parts by mass, based on 100 parts by mass of the acrylic adhesive polymer (A).

[0079] Other additives that may be blended in the composition include, for example, antioxidants, ultraviolet absorbers, antiaging agents, flame retardants, antifungal agents, silane coupling agents, fillers, colorants, etc. The content of the additives can be appropriately set depending on the various compounds within a range that does not impair the effects of the present invention.

[0080] When the present composition is a solvent-based composition, the solid content concentration in the pressure-sensitive adhesive composition (i.e., the ratio of the mass of components other than the solvent in the pressure-sensitive adhesive composition to the total mass of the pressure-sensitive adhesive composition) is not particularly limited, but is preferably 1 to 70 mass%. When the solid content concentration is 1 mass% or more, a pressure-sensitive adhesive layer having a sufficient thickness can be formed. When the solid content concentration is 70 mass% or less, good coating properties can be ensured, and a pressure-sensitive adhesive layer of uniform thickness can be easily formed. The solid content concentration in the present composition is more preferably 5 to 50 mass%, and even more preferably 10 to 45 mass%.

[0081] The viscosity of the present composition is preferably 500 to 10,000 mPa·s. When the viscosity is 10,000 mPa·s or less, good coatability can be ensured. In addition, the composition can be used as it is without diluting it to a viscosity suitable for coating, and the handling is good. From this viewpoint, the viscosity of the present composition is more preferably 8,000 mPa·s or less, and even more preferably 6,000 mPa·s or less. In addition, the lower limit of the viscosity of the present composition is more preferably 1,000 mPa·s or more, and even more preferably 1,500 mPa·s or more, from the viewpoint of suppressing the film thickness from becoming too thin. The viscosity of the adhesive composition is a value measured at 25°C using a B-type viscometer for an adhesive composition having a solid content concentration of 25%.

[0082] <Method of forming pressure-sensitive adhesive layer> The adhesive layer in the present pressure-sensitive adhesive sheet can be formed by applying the present composition to a separator or the like and drying it as necessary. As the separator, a resin film made of various resin materials can be used. Examples of the resin material constituting the resin film include polyester resins such as polyethylene terephthalate, polyethersulfone resins, acetate resins, polycarbonate resins, polyolefin resins, and the like.

[0083] When forming a pressure-sensitive adhesive layer using a solvent-based pressure-sensitive adhesive composition, the composition is first applied to a separator by a known coating method, and the solvent is preferably removed by drying treatment such as heating. The heating temperature and heating time when forming the pressure-sensitive adhesive layer may be appropriately set according to the type of solvent contained in the composition, the solid content concentration, etc., as long as the solvent can be removed. The thickness of the pressure-sensitive adhesive layer is, for example, 2 to 150 μm, preferably 2 to 100 μm, and more preferably 2 to 75 μm. In addition, in order to obtain a pressure-sensitive adhesive layer with a desired thickness, the pressure-sensitive adhesive layer may be formed by laminating a plurality of thin films.

[0084] In the manufacturing process for obtaining the present pressure-sensitive adhesive sheet, the present composition may be applied to a separator or the like, and the pressure-sensitive adhesive layer after removing the solvent as necessary may be irradiated with active energy rays to perform pre-crosslinking. However, in the treatment of irradiating with active energy rays in the manufacturing process for the present pressure-sensitive adhesive sheet, the irradiation amount of the active energy rays, etc. is appropriately set so that the gel fraction based on the acrylic adhesive polymer (A) in the pressure-sensitive adhesive layer is 20% or more and 90% or less, preferably 80% or less, more preferably 70% or less.

[0085] One embodiment of the present pressure-sensitive adhesive sheet thus obtained is a so-called substrate-less embodiment in which a pressure-sensitive adhesive layer is sandwiched between two separators having the same or different peel strengths, as shown in Fig. 1. The pressure-sensitive adhesive sheet 10 in Fig. 1 is a laminate in which a first separator 11, a pressure-sensitive adhesive layer 12, and a second separator 13 are laminated in this order. It is preferable that the first separator 11 and the second separator 13 have different releasability. For example, the first separator 11 may be a heavy release film, and the second separator 13 may be a light release film.

[0086] The pressure-sensitive adhesive sheet may have a structure in which a substrate is disposed on one side of the pressure-sensitive adhesive layer and a separator is disposed on the other side. The shape of the pressure-sensitive adhesive sheet is not particularly limited and may be appropriately set according to the mode of use. The pressure-sensitive adhesive sheet may be, for example, in the form of a sheet, in the form of a roll, or cut into strips. It may also have any shape according to the bonding location. One embodiment of the pressure-sensitive adhesive sheet is a pressure-sensitive adhesive tape.

[0087] <Physical properties of adhesive layer> ·Weight reduction rate The adhesive layer of the present adhesive sheet preferably has a weight loss rate of 5% by weight or less at 200°C measured by thermogravimetry under conditions of a temperature rise rate of 20°C / min and a temperature rise range of 25 to 350°C. If the weight loss rate is 5% by weight or less, when the adhesive sheet is subjected to a thermal load, the adhesive layer is less likely to volatilize components, and the adhesive sheet can have high heat resistance in which foaming and lifting due to thermal load are suppressed. From the viewpoint of improving the heat resistance of the adhesive sheet, the weight loss rate measured under the above conditions is more preferably 4% by weight or less, and even more preferably 3% by weight or less. In this specification, the method for measuring the weight loss rate of the adhesive layer by thermogravimetry follows the method described in the Examples below.

[0088] Peel strength The adhesive sheet of the present invention exhibits easy peelability by irradiating the adhesive layer with active energy rays after bonding the adhesive layer to the adherend and crosslinking or further crosslinking the acrylic adhesive polymer (A), thereby reducing the adhesive strength. When comparing the adhesive strength before irradiating the adhesive sheet of the present invention bonded to the adherend (i.e., an adhesive sheet having a gel fraction of the adhesive layer in the range of 20 to 90%) with the adhesive strength after irradiating the adhesive sheet of the present invention bonded to the adherend, it is preferable that the adhesive strength before the irradiation of active energy rays is high, thereby suppressing peeling from the adherend. On the other hand, from the viewpoint of realizing easy peelability by irradiation of active energy rays, it is preferable that the adhesive strength after irradiation of active energy rays is lower than that before the irradiation of active energy rays.

[0089] Specifically, when the ratio (S2 / S1) of the peel strength (referred to as "S1") before the present pressure-sensitive adhesive sheet (i.e., a pressure-sensitive adhesive sheet having a gel fraction of the pressure-sensitive adhesive layer in the range of 20 to 90%) is irradiated with active energy rays and the peel strength (referred to as "S2") after the present pressure-sensitive adhesive sheet is irradiated with active energy rays and the gel fraction based on the acrylic pressure-sensitive adhesive polymer (A) of the pressure-sensitive adhesive layer is made to exceed 90% is used as an index, the ratio (S2 / S1) is preferably 0.7 or less. In terms of being able to further increase the adhesiveness before the irradiation of active energy rays and the easy peelability after the irradiation of active energy rays, the ratio (S2 / S1) is more preferably 0.65 or less, even more preferably 0.6 or less, and even more preferably 0.5 or less. The peel strength is a value measured in accordance with JIS Z-0237. Details of the measurement method are in accordance with the method described in the examples below.

[0090] <Using the adhesive sheet> The pressure-sensitive adhesive sheet is excellent in heat resistance, being unlikely to foam or lift off from the adherend even when heated to high temperatures (e.g., 200°C or higher). Therefore, the pressure-sensitive adhesive sheet is suitable as a pressure-sensitive adhesive sheet used in semiconductor manufacturing processes (i.e., a pressure-sensitive adhesive sheet for semiconductor manufacturing processes). The pressure-sensitive adhesive sheet also exhibits easy peelability when irradiated with active energy rays after being attached to an adherend. The pressure-sensitive adhesive sheet is used for the purpose of temporarily fixing an adherend or protecting the adherend surface in semiconductor manufacturing processes, and is suitable for applications in which it is required to peel off the pressure-sensitive adhesive layer by irradiating the pressure-sensitive adhesive layer with active energy rays when temporary fixation and surface protection by the pressure-sensitive adhesive layer are no longer required.

[0091] For example, in a semiconductor manufacturing process using FOWLP technology or three-dimensional integrated semiconductor (3D-IC) technology, an adhesive tape is attached to a support substrate (e.g., a glass substrate), a semiconductor chip is placed on the adhesive layer of the adhesive tape attached to the support substrate, and the semiconductor chip is temporarily fixed on the support substrate, and then various lamination processes are performed to form a laminate on the support substrate, and then the support substrate and the adhesive layer are peeled off. The present adhesive sheet can be preferably used as the adhesive tape in such a manufacturing process.

[0092] Examples of the active energy ray irradiated when peeling off the pressure-sensitive adhesive sheet include ultraviolet light, visible light, and electron beams. Of these, ultraviolet light or electron beams are preferred. The irradiation energy of the active energy ray can be appropriately set depending on the type of active energy ray and the composition of the pressure-sensitive adhesive layer.

[0093] For example, when ultraviolet rays are used as the active energy rays, the wavelength is, for example, 250 to 400 nm. Examples of ultraviolet ray irradiation devices include high-pressure mercury lamps, metal halide lamps, ultraviolet electrodeless lamps, and ultraviolet light-emitting diodes (UV-LEDs). The integrated light amount of ultraviolet rays with a wavelength of 365 nm is 500 mJ / cm. 2 More than 1,000 mJ / cm is preferable. 2 More preferably, 1,500 mJ / cm 2The upper limit of the accumulated light amount is preferably 100,000 mJ / cm from the viewpoint of minimizing the influence on each component in the pressure-sensitive adhesive layer and from the viewpoint of reducing energy. 2 Less than 50,000 mJ / cm is preferable. 2 The following is more preferred:

[0094] The illuminance and irradiation time of the ultraviolet light can be appropriately set so that the integrated light amount is the desired amount. For example, the illuminance of ultraviolet light with a wavelength of 365 nm is 1.0 mW / cm 2 More than 2.0mW / cm is preferable. 2 More preferably, 3.0 mW / cm 2 More preferably, the upper limit of the illuminance is 3,000 mW / cm 2 Less than 2,000 mW / cm is preferable. 2 Less than 1,000 mW / cm is more preferable. 2 The following is even more preferred:

[0095] When an electron beam is used as the active energy beam, the electron beam irradiation device is not particularly limited, but examples thereof include Cockcroft-Walton type, Van de Graaff type, and resonant transformer type devices. The absorbed dose of the electron beam is preferably 1 to 200 kGy, more preferably 10 to 100 kGy. The acceleration voltage of the electron beam may be appropriately set within a range of 80 to 300 kV depending on the film thickness of the substrate. The oxygen concentration of the electron beam irradiation atmosphere is preferably 500 ppm or less, more preferably 300 ppm or less.

[0096] An example of the case where a laminate is produced using the pressure-sensitive adhesive sheet in a semiconductor manufacturing process is shown in Figure 2. Here, a case where an encapsulated semiconductor body including a semiconductor chip and an encapsulating layer is produced as the laminate is described.

[0097] First, the first separator 11 is peeled off from the adhesive sheet 10 shown in FIG. 1, and the adhesive sheet 10 is attached to the glass substrate 21 so that the surface of the adhesive layer 12 of the adhesive sheet 10 is in contact with the surface of the glass substrate 21. After that, the second separator 13 is peeled off to expose the surface of the adhesive layer 12 (see FIG. 2(a)). Next, the semiconductor chip 22 is placed on the adhesive layer 12, and the semiconductor chip 22 is temporarily fixed on the glass substrate 21 (see FIG. 2(b)). Furthermore, a sealing layer 23 is formed so as to cover the surface of the glass substrate 21 and the semiconductor chip 22. As a result, a semiconductor sealed body 24 in which the semiconductor chip 22 is sealed by the sealing layer 23 on the glass substrate 21 is obtained (see FIG. 2(c)). The material for forming the sealing layer 23 is not particularly limited, and for example, an epoxy resin or the like is used.

[0098] Thereafter, the laminate of glass substrate 21 and semiconductor encapsulated body 24 is irradiated with active energy rays. This reduces the adhesive strength of adhesive layer 12, and allows semiconductor encapsulated body 24 to be peeled off from glass substrate 21 at interface 25 between semiconductor encapsulated body 24 and adhesive layer 12 (see FIGS. 2(c) and (d)). EXAMPLES

[0099] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to these examples. In the following, "parts" and "%" mean "parts by mass" and "% by mass", respectively, unless otherwise specified. The analysis methods for the polymers used in the examples and comparative examples are as follows.

[0100] <Molecular weight measurement> Using a gel permeation chromatograph (model name "HLC-8320", manufactured by Tosoh Corporation), the number average molecular weight (Mn) and weight average molecular weight (Mw) were obtained in terms of polystyrene under the following conditions. The molecular weight distribution (Mw / Mn) was calculated from the obtained values. Measurement conditions Column: Tosoh TSKgel SuperMultiporeHZ-M x 4 Column temperature: 40℃ Eluent: Tetrahydrofuran Detector: RI Flow rate: 600μL / min

[0101] <Measurement of glass transition temperature (Tg)> The glass transition temperature (Tg) of the polymer was determined from the intersection of the baseline of the heat flux curve obtained using a differential scanning calorimeter and the tangent at the inflection point. The heat flux curve was obtained by heating about 10 mg of a sample from room temperature (25°C) to 150°C at 10°C / min, subsequently cooling to -100°C, holding for 5 minutes, and then heating to 150°C at 10°C / min. Measuring equipment: SII NanoTechnology DSC6220 Measurement atmosphere: Nitrogen atmosphere

[0102] <Calculation of monomer composition of polymer> The monomer composition of the polymer was calculated from the charged amounts and the consumed amounts of monomers measured by gas chromatography (GC).

[0103] 1. Synthesis of acrylic adhesive polymer [Synthesis Example 1] Polymer A-1 used in Example 1 Into a 1-liter four-neck flask, methyl acrylate (hereinafter also referred to as "MA") (132 parts by mass), 2-ethylhexyl EO-modified (n≒2) acrylate (trade name "Aronix M-120", manufactured by Toagosei Co., Ltd., hereinafter also referred to as "M-120") (127 parts by mass), 4-hydroxybutyl acrylate (hereinafter also referred to as "4HBA") (14 parts by mass), and ethyl acetate (320 parts by mass) were charged. This mixture was thoroughly degassed by bubbling nitrogen gas, the internal temperature of the mixture was raised to 75°C, and 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., hereinafter also referred to as "V-65") (0.17 parts by mass) was charged to initiate polymerization. After 5 hours, ethyl acetate was added so that the solid content was 30% by mass, and an ethyl acetate solution of polymer A-1 was obtained. The obtained polymer A-1 was composed of 50 mass % of MA, 45 mass % of M-120, and 5 mass % of 4HBA, and had Mw of 560,000, Mw / Mn of 4.1, and Tg of -34°C.

[0104] [Synthesis Example 2] Polymer A-2 used in Comparative Example 1 In a 3-liter four-neck flask, n-butyl acrylate (hereinafter also referred to as "BA") (90 parts by mass), 2-methoxyethyl acrylate (hereinafter also referred to as "C1") (413 parts by mass), 2-hydroxyethyl acrylate (hereinafter also referred to as "HEA") (27 parts by mass), and ethyl acetate (980 parts by mass) were charged. This mixture was thoroughly degassed by bubbling nitrogen gas, the internal temperature of the mixture was raised to 75°C, and V-65 (0.25 parts by mass) was charged to start polymerization. After 5 hours, ethyl acetate was added so that the solid content was 30% by mass, and an ethyl acetate solution of polymer A-2 was obtained. The obtained polymer A-2 consisted of 17% by mass of BA, 78% by mass of C1, and 5% by mass of HEA, and had Mw of 570,000, Mw / Mn of 3.6, and Tg of -35°C.

[0105] [Synthesis Example 3] Polymer A-3 used in Comparative Example 2 BA (476 parts by mass), HEA (24 parts by mass), and ethyl acetate (930 parts by mass) were charged into a 3-liter four-neck flask. The mixture was thoroughly degassed by bubbling nitrogen gas, the internal temperature of the mixture was raised to 75°C, and V-65 (0.24 parts by mass) was charged to initiate polymerization. After 5 hours, ethyl acetate was added so that the solid content was 30% by mass, and an ethyl acetate solution of polymer A-3 was obtained. The obtained polymer A-3 was composed of 95% by mass of BA and 5% by mass of HEA, and had Mw of 480,000, Mw / Mn of 4.0, and Tg of -52°C.

[0106] 2. Preparation of adhesive composition and production of adhesive sheet [Example 1] To the ethyl acetate solution of polymer A-1 obtained in Synthesis Example 1, a hydrogen abstraction type photopolymerization initiator "Omnipol BP" (manufactured by IGM RESINS) was added in an amount of 10 parts by mass relative to polymer A-1 (100 parts by mass in terms of solid content), and an isocyanate-based curing agent "Takenate D-110N" (manufactured by Mitsui Chemicals) was added in an amount of 0.4 parts by mass (solid content) relative to polymer A-1 (100 parts by mass in terms of solid content) as a crosslinking agent, to prepare a pressure-sensitive adhesive composition. This adhesive composition was applied onto a 38 μm thick polyethylene terephthalate (hereinafter also referred to as "PET") separator so that the thickness after drying would be 40 μm. The adhesive composition was dried at 100° C. for 4 minutes to remove ethyl acetate. Thereafter, a 38 μm thick PET separator with a different peel strength from the separator was attached, and the resulting sheet was left to stand at 40° C. for 5 days for aging, thereby obtaining a crosslinked adhesive sheet sample with a double-sided separator. The obtained adhesive sheet sample was used to carry out various evaluations by the methods described below.

[0107] <Evaluation method> Gel fraction measurement 0.2 g of adhesive was collected from the adhesive layer of the adhesive sheet sample (i.e., the adhesive sheet before being attached to the adherend), and the initial mass of the adhesive was weighed. The adhesive was immersed in 50 g of ethyl acetate and allowed to stand at room temperature for 16 hours. It was then filtered through a 200 mesh wire net, and the residue remaining on the mesh was dried at 80°C for 3 hours and weighed. The gel fraction based on the acrylic adhesive polymer was calculated from the initial mass and the mass of the residue using the following formula. Gel fraction (%)=(mass of residue) / [(initial mass)×(solid content of acrylic adhesive polymer) / (solid content of entire adhesive composition)]×100

[0108] -Evaluation of peelability The adhesive sheet sample was transferred onto a polyimide film (Apical (registered trademark), 25 μm thick, manufactured by Kaneka Corporation) to obtain a first adhesive sheet for evaluation. A glass plate (Fabritech FL11A, 1 mm thick, manufactured by AGC Corporation) was used as an adherend, and the first adhesive sheet for evaluation was attached to the glass plate to obtain a laminate of glass plate / adhesive layer / polyimide film. After manual attachment with a hand roller, the 180-degree peel strength of the first adhesive sheet for evaluation was measured at 23° C. using a tensile tester (Autograph AGS, manufactured by Shimadzu Corporation) in accordance with JIS Z-0237 "Test method for adhesive tapes and adhesive sheets". The peel speed was 300 mm / min. This measured value was taken as the peel strength S1 before UV irradiation. Separately, the adhesive sheet sample was transferred to a polyimide film (Apical (registered trademark), 25 μm thick, manufactured by Kaneka Corporation) to obtain a second adhesive sheet for evaluation. A glass plate (Fabritech FL11A, 1 mm thick, manufactured by AGC Corporation) was used as the adherend, and the second adhesive sheet for evaluation was attached to the glass plate to obtain a laminate of glass plate / adhesive layer / polyimide film. After manual attachment with a hand roller, ultraviolet light with a wavelength of 365 nm was applied from the glass plate side at room temperature (25° C.) at 3,000 mJ / cm using a UV irradiator (Mini Grandage ECS-1511U, with metal halide lamp, manufactured by iGraphics Co., Ltd.). 2 The second evaluation pressure-sensitive adhesive sheet was then irradiated with an exposure dose of 180°. The 180° peel strength of the second evaluation pressure-sensitive adhesive sheet was then measured in the same manner as above, and this was designated as the peel strength S2 after UV irradiation. The gel fraction of the second evaluation pressure-sensitive adhesive sheet after UV irradiation was measured by the above-mentioned method, and was found to be over 90%. The ratio (S2 / S1) of the peel strength S2 after UV irradiation to the peel strength S1 before UV irradiation was determined, and the ease of peeling was evaluated according to the following criteria. ○: S2 / S1 is 0.7 or less ×: S2 / S1 is greater than 0.7

[0109] -Heat resistance evaluation (heating test) Two glass plates (size 30 mm x 50 mm, thickness 0.15 mm) were used as adherends, and the separator was peeled off from the adhesive sheet sample and hand-attached to the glass plates with a hand roller to obtain a laminate of glass plate / adhesive layer / glass plate. The laminate was heated on a hot plate at 200°C for 10 minutes. The appearance of the laminate after heating was visually observed, and the heat resistance was evaluated according to the following criteria. Note that the smaller the size of the bubbles and the fewer the number of bubbles, the less foaming and peeling from the adhesive layer due to heating, indicating better heat resistance. ○: No bubbles of 1mm or more ×: Bubbles of 1mm or more present

[0110] -Evaluation of heat resistance (thermogravimetry) The separator was peeled off from the pressure-sensitive adhesive sheet sample, and the pressure-sensitive adhesive layer alone was weighed in an aluminum pan, and the aluminum pan was set in a thermogravimetric analyzer (TG / DTA, STA2500Regulus type, manufactured by NETZSCH). The measurement sample was heated from 25°C to 350°C at a heating rate of 20°C / min in a nitrogen atmosphere using the thermogravimetric analyzer, and the weight loss rate at 200°C was measured. The heat resistance of the pressure-sensitive adhesive layer was evaluated according to the following criteria based on the measured weight loss rate. The smaller the weight loss rate, the less foaming occurred when the pressure-sensitive adhesive layer was subjected to a heat load, indicating better heat resistance. ○: Weight loss rate is 5% or less ×: Weight loss rate exceeds 5% by weight

[0111] [Example 2] An adhesive composition was produced in the same manner as in Example 1, except that the amount of the photopolymerization initiator "Omnipol BP" added was 20 parts by mass per 100 parts by mass of the acrylic adhesive polymer, and various evaluations were performed in the same manner as in Example 1.

[0112] [Comparative Example 1] A pressure-sensitive adhesive composition was produced by the same procedure as in Example 1, except that polymer A-2 obtained in Synthesis Example 2 was used instead of polymer A-1, and the photopolymerization initiator "Omnipol BP" was not added, and various evaluations were performed in the same manner as in Example 1. [Comparative Example 2] A pressure-sensitive adhesive composition was produced by the same procedure as in Example 1, except that polymer A-3 obtained in Synthesis Example 3 was used instead of polymer A-1, and the photopolymerization initiator "Omnipol BP" was not added, and various evaluations were performed in the same manner as in Example 1.

[0113] [Comparative Example 3] An adhesive composition was produced by the same procedure as in Example 1, except that the isocyanate-based curing agent "Takenate D-110N" (manufactured by Mitsui Chemicals, Inc.) was not added as a crosslinking agent, and various evaluations were performed in the same manner as in Example 1. [Comparative Example 4] A pressure-sensitive adhesive composition was produced by the same procedure as in Example 1, except that 4.0 parts by mass (solid content) of the crosslinking agent was added to polymer A-1 (100 parts by mass in terms of solid content), and various evaluations were performed in the same manner as in Example 1.

[0114] The ingredients and evaluation results of the pressure-sensitive adhesive compositions of Examples 1 and 2 and Comparative Examples 1 to 4 are shown in Table 1.

[0115] [Table 1]

[0116] The abbreviations in Table 1 represent the following names. MA: Methyl acrylate (boiling point 80°C) M-120: 2-ethylhexyl EO modified (n≒2) acrylate, product name "Aronix M-120", manufactured by Toagosei Co., Ltd. (boiling point 340°C) BA: n-butyl acrylate (boiling point 145°C) C1: 2-Methoxyethyl acrylate (boiling point 151°C) 4HBA: 4-hydroxybutyl acrylate (boiling point 298°C) HEA: 2-hydroxyethyl acrylate (boiling point 196°C) BP: Hydrogen abstraction type photopolymerization initiator, product name "Omnipol BP", manufactured by IGM RESINS D-110N: Isocyanate-based hardener, product name "Takenate D-110N", manufactured by Mitsui Chemicals The amounts of crosslinking agent and photopolymerization initiator are based on 100 parts by mass of acrylic adhesive polymer. The boiling points of the monomers are predicted values ​​under atmospheric pressure calculated by Fujitsu Ltd.'s Scientific Research Information Management Solution (ACD / Labs). The boiling points (predicted values) of each monomer are also shown in Table 1.

[0117] As shown in Table 1, all of the adhesive sheets of Examples 1 and 2, which were produced using an adhesive composition containing polymer A-1 as an acrylic adhesive polymer and a hydrogen abstraction type photopolymerization initiator and had an adhesive layer with a gel fraction of 70% or 68%, had good peelability and heat resistance.

[0118] In contrast, the adhesive sheets of Comparative Example 1 and Comparative Example 2, in which no hydrogen abstraction type photopolymerization initiator was added to the adhesive composition, were both rated as "x" for ease of peeling and heat resistance. This result is believed to be due to the fact that, since no hydrogen abstraction type photopolymerization initiator was added to the adhesive composition in Comparative Example 1 and Comparative Example 2, the crosslinking reaction did not proceed sufficiently even when the adhesive layer was irradiated with UV after being attached to the adherend, and as a result, the peel strength S2 did not decrease sufficiently, resulting in insufficient ease of peeling. In addition, the polymer A-2 used in Comparative Example 1 and the polymer A-3 used in Comparative Example 2 contain a large amount of monomer components whose boiling points are higher than 100°C and lower than 200°C, which is also believed to be one of the reasons for the insufficient heat resistance. In addition, the adhesive sheet of Comparative Example 3, which has a gel fraction of 0%, was rated as "x" for heat resistance, and the adhesive sheet of Comparative Example 4, which has a gel fraction of 91%, was rated as "x" for ease of peeling. [Explanation of symbols]

[0119] REFERENCE SIGNS LIST 10...adhesive sheet, 11...first separator, 12...adhesive layer, 13...second separator, 21...glass substrate, 22...semiconductor chip, 23...sealing layer, 24...semiconductor encapsulant, 25...interface

Claims

1. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer is formed from an active energy ray-curable pressure-sensitive adhesive composition that contains an acrylic pressure-sensitive adhesive polymer (A) and a hydrogen abstraction type photopolymerization initiator, and does not contain a compound having two or more reactive unsaturated bonds in one molecule; The acrylic adhesive polymer (A) has at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon, a secondary amino group, and a tertiary amino group in a side chain, the content of the hydrogen abstraction photopolymerization initiator in the active energy ray-curable pressure-sensitive adhesive composition is 0.1 parts by mass or more and 50 parts by mass or less based on 100 parts by mass of the acrylic pressure-sensitive adhesive polymer (A); A pressure-sensitive adhesive sheet, wherein the pressure-sensitive adhesive layer has a gel fraction based on the acrylic pressure-sensitive adhesive polymer (A) of 20% or more and 90% or less before being attached to an adherend.

2. The acrylic adhesive polymer (A) contains a structural unit (U) derived from a (meth)acrylic monomer having at least one selected from the group consisting of an ether group, a hydroxyl group, an aliphatic tertiary carbon (excluding the carbon atom constituting the carbon-carbon double bond in a methacryloyl group), a secondary amino group, and a tertiary amino group, The pressure-sensitive adhesive sheet according to claim 1 , wherein a content ratio of the structural unit (U) in the acrylic pressure-sensitive adhesive polymer (A) is 10 mass % or more based on all structural units of the acrylic pressure-sensitive adhesive polymer (A).

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the acrylic pressure-sensitive adhesive polymer (A) contains a structural unit derived from a monomer represented by the following formula (1): CH 2 =CR 1 -C(=O)O-(R 2 O) n -R 3 …(1) (In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a linear or branched alkylene group having 2 to 6 carbon atoms; R 3 represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 20 carbon atoms, and n represents an integer of 2 to 100.

4. The pressure-sensitive adhesive sheet according to claim 1, wherein the acrylic pressure-sensitive adhesive polymer (A) has a glass transition temperature of -50°C or higher and 0°C or lower.

5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the acrylic pressure-sensitive adhesive polymer (A) has a weight average molecular weight of 100,000 or more.

6. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the acrylic adhesive polymer (A) contains structural units derived from at least one selected from the group consisting of (meth)acrylic monomers having a boiling point of 100° C. or less and (meth)acrylic monomers having a boiling point of 200° C. or more in an amount of 50 mass% or more relative to all structural units of the acrylic adhesive polymer (A).

7. The pressure-sensitive adhesive sheet according to claim 1 , wherein the active energy ray-curable pressure-sensitive adhesive composition further contains a crosslinking agent.

8. The pressure-sensitive adhesive sheet according to claim 1, wherein the pressure-sensitive adhesive layer has a weight loss rate of 5% by weight or less at 200° C., as measured by thermogravimetry under conditions of a heating rate of 20° C. / min and a heating range of 25 to 350° C.

9. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the ratio (S2 / S1) of the peel strength (S1) before the pressure-sensitive adhesive sheet attached to the adherend is irradiated with active energy rays to the peel strength (S2) after the pressure-sensitive adhesive sheet attached to the adherend is irradiated with active energy rays to increase the gel fraction based on the acrylic adhesive polymer (A) of the pressure-sensitive adhesive layer to more than 90% is 0.7 or less.

10. The pressure-sensitive adhesive sheet according to any one of claims 1 to 9, which is for use in a semiconductor manufacturing process.

Citation Information

Patent Citations

  • Heat-resistant temporary adhesion adhesive tape

    JP2012031316A

  • Adhesive tape

    JP2016089045A